A enzima histidinol desidrogenase de Mycobacterium tuberculosis como alvo macromolecular para o planejamento de novos candidatos a fármacos para o tratamento da tuberculose - Lunardi, Juleane (2015)
the second responsible for most of the deaths worldwide. The latest estimates of WHO showed that 9 millions of new cases of TB occurred in 2013 and 1.5 million of deaths. The emergence of new drug resistant M. tuberculosis strains is becoming a serious increasing problem as the treatment of infected patients with multi drug-resistant TB and extensively drug-resistant TB strains is much more difficult and costly. This brings discussions about the drastic situation of virtually untreatable TB cases and shows the urgent need to introduce new and effective anti-TB drugs. The research for the development of new antimycobacterial agents becomes a necessity, as well as the identification of new targets for future drugs. The histidine biosynthetic pathway is comprised of ten enzyme steps catalyzed by eight enzymes. This pathway is present in prokaryotic organisms, lower eukaryotic organisms and plants, but is absent in animals, which is in accordance with the principles of selective toxicity. Mutagenesis studies have shown that the genes of this pathway are essential for the survival of M. tuberculosis. The histidinol dehydrogenase enzyme, encoded by hisD, performs the last two steps in the biosynthesis of histidine, converting L-histidinol to L-histidine. The essentiality of the hisD gene in M. tuberculosis mutants with referred gene knockout is already described in the literature. This work describes kinetic studies using thermodynamic parameters, fluorescence spectroscopy, and pre-stationary states to better understand the enzymatic mechanism of MtHisD. Characterization of the reaction catalyzed by mycobacterial HisD is important to structure-based drug development. The data from enzyme’s kinetic characterization were the starting point for HisD specific inhibitors planning, selection, and testing. A series of eleven hydrazones derived from L-histidine was synthesized, from which four compounds were identified as showing a competitive inhibition profile for L-histidinol substrate. The interactions of these compounds with the enzyme were analyzed by molecular docking to understand the inhibitory mechanism. Results from this work are believed to enhance the understanding of mycobacterial histidine metabolism. Moreover, data from inhibition studies with the synthesized compounds, serve as the starting point for the development of new molecules to enhance the enzyme inhibition and to inhibit the M. tuberculosis growth.